Does maternal stress drive offspring dispersal in an asocial mammal? - Kanaziz, Rachel, author; Huyvaert, Kate P., author; Wells-Salerno, Caitlin, author; Kepas, Megen, author; Hudson, Spencer, author; French, Susannah S., author; Aubry, Lise M., author (Colorado State University. Libraries, 2019)
Stress is a physiological state experienced by all living organisms which can be passed across generations. The purpose of my study is to understand the consequences of maternal nutritional stress on daughter dispersal behavior (i.e. remain philopatric or disperse away from the natal home range). I address this in a population of golden mantled ground squirrels (GMGS), Callospermophilus lateralis, which has been studied for 30 years at Rocky Mountain Biological Research Laboratory in Gothic, Colorado. These hibernating mammals give birth to their young in burrows and offspring suckle from their mothers until emergence. During lactation, the stress hormone corticosterone can be transmitted from mother to offspring where it is eventually uptaken by developing hair follicles. By capturing and collecting hair samples from all mothers and daughters immediately upon emergence, stress data from the hair samples can be paired with philopatric/dispersal behavioral data to determine whether the nutritional stress of mothers determines if daughters remain philopatric or disperse after weaning. Sons tend to disperse regardless of circumstances whereas daughters sometimes remain philopatric to their natal home range. The ultimate goal of my thesis research is to gain insight into the role mother-daughter bonds play in shaping offspring behavior and fitness in light of environmental stress.
140 - Rachel Kanaziz
Maternal stress and offspring philopatric behavior in an asocial mammal
Rachel Kanaziz, Kate P. Huyvaert, Caitlin Wells-Salerno, and Lise Aubry affiliated with the Graduate Degree Program in Ecology, Department of Fish, Wildlife, and Conservation Biology, Colorado State University.
Megen Kepas, Spencer Hudson, and Susannah S. French affiliated with the Biology Department, Utah State University.
Keywords: corticosterone; dispersal; golden mantled ground squirrel; stress; philopatry